The Effect Of Organizational Justice And The Ability To Manage Conflicts Of Interest On Organizational Commitment And Its Implications On Sustainable Human Resource Performance In Mining Companies In East Kalimantan - Jonedi Tuling; Tata Rustandi; Khaeruman Khaeruman (JURNAL ECONOMINA, 2026)
The problem of this research departs from the low performance of sustainable human resources (HR) in mining companies in East Kalimantan. This phenomenon is characterized by high turnover rates, low employee engagement, weak conflict of interest management, and low perception of organizational fairness. This condition indicates structural and psychosocial problems that hinder the formation of strong organizational commitments, which ultimately leads to a decline in long-term performance consistency. This research is directed to explore the impact of organizational justice and ability to manage conflicts of interest on organizational commitments, as well as its implications for the sustainability of human resource (HR) performance in the mining sector in East Kalimantan. In addition, this study investigates the function of organizational commitment as a mediator in the relationship between organizational justice, conflict of interest management, and sustainable human resource performance. Quantitative methods are used, with a correlational research design. This study involved all employees of mining companies totaling 1,669 people; The proportional random sampling technique was used to sample as many as 190 people from them. The data collection tool is a questionnaire created based on theoretical indicators for each variable. The direct and indirect relationships between variables were tested using Structural Equation Modeling (SEM) using a Smart PLS device for data analysis. The results of the study show that organizational fairness benefits organizational commitment and HR performance. In addition, the ability to manage conflicts of interest also benefits organizational commitment and human resource performance. In addition, organizational commitment benefits overall HR performance. In addition, organizational commitment as a mediation variable has an indirect impact on organizational justice and the ability to manage conflicts of interest on performance. This research shows that sustainable improvement of human resource performance does not only depend on technical components, but also requires the improvement of psychosocial elements such as conflict of interest management and organizational justice. Therefore, mining companies in East Kalimantan must create a fair and transparent system and implement a collaborative conflict management strategy. Ultimately, these measures will result in a high organizational commitment, which will ensure the sustainability of human resource performance and support the achievement of long-term business targets and compliance with sustainability (ESG) principles